Freedom Time : Negritude, Decolonization, and the Future of the World - Wilder, Gary (Book collections on Project MUSE., 2015)
Freedom Time reconsiders decolonization from the perspectives of Aime Cesaire (Martinique) and Leopold Sedar Senghor (Senegal) who, beginning in 1945, promoted self-determination without state sovereignty. As politicians, public intellectuals, and poets they struggled to transform imperial France into a democratic federation, with former colonies as autonomous members of a transcontinental polity. In so doing, they revitalized past but unrealized political projects and anticipated impossible futures by acting as if they had already arrived. Refusing to reduce colonial emancipation to national independence, they regarded decolonization as an opportunity to remake the world, reconcile peoples, and realize humanity's potential. Emphasizing the link between politics and aesthetics, Gary Wilder reads Cesaire and Senghor as pragmatic utopians, situated humanists, and concrete cosmopolitans whose postwar insights can illuminate current debates about self-management, postnational politics, and planetary solidarity. Freedom Time invites scholars to decolonize intellectual history and globalize critical theory, to analyze the temporal dimensions of political life, and to question the territorialist assumptions of contemporary historiography. -- from back cover.